Poly(ether ether ketone)s and poly(ether ether ketone ketone)s containing cardo decahydronaphthalene groups: synthesis and characterization - Honkhambe, Pandurang N.; Pasale, Sharad K.; Bhairamadgi, Nagendra S.; Kumbhar, Kishor P.; Salunkhe, Manikrao M.; Wadgaonkar, Prakash P. (Journal of Applied Polymer Science, 2011)
New poly(ether ether ketone)s and poly (ether ether ketone ketone) s were synthesized by polycondensation of each of the three bisphenols, viz., 4,4'-(octahydro-2(1H)-naphthylidene) bisphenol, 4,4'-(octa-hydro-2(1H)-naphthylidene) bis-3-methylphenol, and 4,4'(octahydro-2(1H)-naphthylidene) bis-3,5-dimethylphenol with 4,4'-difluorobenzophenone and 1,3-bis(4-fluorobenzoyl) benzene in a mixture of N,N-dimethylacetamide and toluene [1 : 1 (v/v)] in the presence of anhydrous potassium carbonate. Inherent viscosities of poly(ether ether ketone) s and poly (ether ether ketone ketone) s were in the range 0.32-0.80 dL/g and number-average molecular weights were in the range 16,100-55,900 g/mol. Poly(ether ether ketone) s and poly(ether ether ketone ketone) s were soluble in organic solvents such as dichloromethane, chloroform, tetrahydrofuran, meta-cresol, pyridine, and 1-methyl-2-pyrrolidinone at room temperature and could be cast into tough, transparent, and flexible films from their chloroform solutions. Wide angle x-ray diffraction measurements revealed the amorphous nature of poly(ether ether ketone) s and poly (ether ether ketone ketone) s. The glass transition temperature poly(ether ether ketone) s and poly(ether ether ketone ketone) s were in the range 185-251 degrees C. The temperature at 10% weight loss, determined from thermogravimetric analysis, of poly(ether ether ketone) s and poly(ether ether ketone ketone) s in nitrogen atmosphere was in the range 462-493 degrees C indicating their good thermal stability. (C) 2011 Wiley Periodicals, Inc. J Appl Polym Sci 122: 1607-1613, 2011
Keywords: bisphenol; cardo decahydronaphthalene; poly(ether ether ketone ketone)s; poly(ether ether ketone)s; Polycondensation; Thermal properties